Zeolite (ZSM-5) as a Highly Efficient and Heterogeneous Catalyst for the Synthesis of β-Enaminones and β-Enamino Esters - Amiya Shekhar; Devendra Deo Pathak (E-Journal of Chemistry)
Several β-enaminones and β-enaminoesters have been synthesized in high yields from amine and β-diketone in the presence of Zeolite (ZSM-5) as a catalyst. This method is applicable to both cyclic and acyclic ketones with aromatic and aliphatic amines.